Equilibrio Parroquial Rural de San Juan y la Responsabilidad del Departamento de Tesorería - Santillán Espinoza, Johanna Paola (2017)
In the present case of study of a financial nature and of social commitment prior to obtaining the title of Engineer in Accounting and Audit, the causes that were evidenced and affected the financial balance of the Autonomous Government of the Parochial Rural District of San Juan were investigated and that in their great majority they originated in the Department of Treasury of such institution. One of the main points analyzed in the present investigation was the verification of the assignments received by the institution, its proper use and accounting record, as well as the different budget reforms that have been applied. On the other hand, it was proceeded to determine the degree of compliance with the norms, laws, procedures and other legal dispositions in force, applied in the execution, reasonableness and sustentation of the expenses executed during a fiscal period. As to the recoverability of the accounts receivable of previous years, the degree of monitoring and purification of the seniority of the same was determined, and the procedures performed, to recover the values ​​for the refund of the value added tax, to the which as Public Sector Institutions are entitled. In addition, the causes and effects of the generation of fines and interest were highlighted by the decentralized Autonomous Government Parochial Rural De San Juan for the delay of its obligations, both with the Ecuadorian Institute of Social Security and with the Internal Revenue Service.